Phylogenetic Analysis of Congenital Rubella Virus from Indonesia: a case report - Herini, Elisabeth Siti; Triono, Agung; Iskandar, Kristy; Nuady, Albaaza; Pujiastuti, Lucia Hetty; Marcellus, Marcellus; Nugrahanto, Andika Priamas; Kamal, Musthofa; Gunadi, Gunadi (BioMed Central Ltd, 2022)
Background: Rubella is a common inherited infection resulting in congenital cataracts and a signifcant cause of permanent vision loss in developing countries. In 2016, Indonesia had the highest number of congenital rubella syndrome (CRS) cases globally. Here, we report the frst genotype of the rubella virus extracted from the eye lens from a child with congenital cataracts due to CRS.